Association of Triglyceride-Glucose (TyG) Index with Diabetic Nephropathy (DN) In Patients of Type II Diabetes Mellitus Presenting in Primary Clinics - Simra Tanveer; Nawaz, Sadaf; Kalroo, Aftab Ali; Paracha, Athar Iqbal; Nazir, Namra; Tahir, Hadia (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the association of triglyceride-glucose (TyG) index with diabetic nephropathy (DN) in patients with type II diabetes mellitus presenting in primary clinicsStudy Design: Cross-sectional study.Place and Duration of Study: Department of Family Medicine, Pak Emirates Military Hospital, Rawalpindi Pakistan, from Oct 2023 to Jan 2024.Methodology: Patients aged between 25 and 60 years, known cases of Type 2 DM, oral hypoglycemics, and reporting to family medicine clinic for their follow-up were included. Samples of 231 patients were collected for serum triglyceride, fasting plasma glucose, and urinary ACR. Patients were divided into DN and non-DN groups based on urinary ACR (cut off